Effects of temperature and phytoplankton community composition on subitaneous and resting egg production rates of Acartia omorii in Tokyo Bay - Ayumi Tsunashima (Nature Portfolio, 2021)
Abstract To clarify the effects of temperature and phytoplankton community composition on Acartia omorii (Copepoda: Calanoida) egg production, its abundance and egg production rates were investigated from 2016 to 2018 in Tokyo Bay, Japan. Abundance was high from March to May (> 3.0 × 104 individuals m−3) and low or undetected from late June to December (≤ 0.4 × 104 individuals m−3). In 2018, most eggs were subitaneous until April; diapause eggs appeared in May when the water temperature exceeded 20 °C. The weight-specific egg production rate (SEPR, Cegg Cfemale −1 day−1) had two peaks. In the first peak in January, > 90% of eggs were subitaneous; in contrast, in the second peak in May, 60% of eggs were unhatched, including diapause eggs. The first peak of subitaneous eggs may contribute to planktonic population development from March to May. In contrast the second peak of diapause eggs probably enhances their recurrence in the next winter. Multiple regression analysis revealed that subitaneous SEPR showed a negative response, whereas diapause SEPR showed a positive response to temperature. Subitaneous SEPR positively correlated with the proportion of small diatoms in phytoplankton carbon biomass, whereas unhatched SEPR positively correlated with the proportion of inedible preys in large diatoms and dinoflagellates. Edible diatoms may induce subitaneous egg production, whereas low-food availability may induce diapause egg production. These results suggest that phytoplankton composition and water temperature have strong impacts on the dynamics of A. omorii via egg production.